2020
DOI: 10.1002/chem.201904635
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Generation and Synthetic Applications of Alkyl‐Substituted Siloxycarbenes: Suppression of Norrish‐Type Fragmentations of Alkanoylsilanes by Triplet Energy Transfer

Abstract: Acylsilanes have been knownt ou ndergo isomerizationt os iloxycarbenesu nder photoirradiation and the thus generated carbenes can be utilized for various synthetic reactions. But this carbene formation is not necessarily efficient with some alkanoylsilanes because Norrishtype fragmentations compete, which limit the synthetic utility of alkanoylsilanes as carbene precursors. In this study,g eneration of siloxycarbenes from alkanoylsilanes by visible-light-inducedenergyt ransfer was examined by using an Ir compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…To circumvent this during the benzoin reaction outlined above, Kusama and co-workers have demonstrated that the desired carbene intermediates can be accessed via triplet-energy transfer using the photosensitiser [Ir(dF(CF 3 )ppy) 2 (dtbbpy)]PF 6 (which is commonly utilised to facilitate triplet-triplet energy transfer processes). [64] This strategy enables irradiation at a higher wavelength to be employed which suppressed Norrish-type fragmentations of alkanoyl silanes and afforded the desired product in higher yield (Scheme 32). Scheme 32.…”
Section: Scheme 27 Siloxy Carbenes React In Intra-and Intermolecular Silyl Acylation Processes With Alkenes and Alkynesmentioning
confidence: 99%
See 1 more Smart Citation
“…To circumvent this during the benzoin reaction outlined above, Kusama and co-workers have demonstrated that the desired carbene intermediates can be accessed via triplet-energy transfer using the photosensitiser [Ir(dF(CF 3 )ppy) 2 (dtbbpy)]PF 6 (which is commonly utilised to facilitate triplet-triplet energy transfer processes). [64] This strategy enables irradiation at a higher wavelength to be employed which suppressed Norrish-type fragmentations of alkanoyl silanes and afforded the desired product in higher yield (Scheme 32). Scheme 32.…”
Section: Scheme 27 Siloxy Carbenes React In Intra-and Intermolecular Silyl Acylation Processes With Alkenes and Alkynesmentioning
confidence: 99%
“…To overcome this, the use of the photosensitiser and higher wavelengths to form the carbene via a triplet-triplet energy transfer process was successfully able to suppress the unwanted side reactions (Scheme 36). [64] Scheme 35. Nucleophilic addition of siloxy carbenes to boronates Scheme 36.…”
Section: Scheme 27 Siloxy Carbenes React In Intra-and Intermolecular Silyl Acylation Processes With Alkenes and Alkynesmentioning
confidence: 99%
“…[7,8] Recently, Kusama and coworkers have reported an elegant method on ZnI 2 assisted photoinduced coupling of acylsilanes with aldehydes with an irradiation of 500 W super-high-pressure Hg lamp. [9] In line with our continuing research interests in the reaction of aldehydes with reactive carbene intermediates, [10] we have unexpectedly uncovered an efficient protocol to prepare α-hydroxyketones through formal cross silyl benzoin reaction between acylsilanes with aldehydes under extremely mild conditions. Compared with Kusama's work, the reaction described in this work could proceed well without addition of any Lewis acid catalysts or photosensitizers.…”
mentioning
confidence: 95%
“…26 We proposed that the [2+1] cyclization reaction between acylsilane-derived carbenes and alkynes might provide a solution for the synthesis of cyclopropenols (Fig- ures 1b and 1c), because acylsilanes are known to be able to produce carbenes on excitation by light. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] However, Bolm and co-workers found that the reactions of alkynes and acylsilanes afforded silylacylation products exclusively, with no [2+1] cyclization products (Figure 1b). 43 In addition, many less-reactive alkynes were tolerated in the intramolecular reactions, 29 but only activated internal alkynes were suitable substrates for the intermolecular reactions.…”
mentioning
confidence: 99%
“…We commenced our study by investigating the conditions for the reaction of phenylacetylene ( 1a ) with the trifluoroacylsilane 2a under irradiation at 460 nm, but the conversion of acylsilane 2a was low, probably because of the low absorption of 2a at 460 nm (Scheme 1 , entry 1). Inspired by the work of the groups of Kusama 34 and Glorius 37 on the generation of siloxycarbenes through triplet-energy-transfer catalysis 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 from alkyl(acyl)silanes, we tested various photosensitizers. We found that 4CzIPN ( E T = 59.6 kcal/mol) 70,71 was a suitable catalyst, and the yield increased to 76% (entry 2).…”
mentioning
confidence: 99%